Diversity and Spatial Heterogeneity of Weed Communities in a Sugarcane Cropping System in the Dry Tropics of Costa Rica - León González, Ramón Gonzalo (2017)
Weed diversity, structure, and distribution within and outside agricultural fields affect not only ecological processes but also weed management strategies. We studied how areas managed differently within and outside the field determine weed communities in a sugarcane cropping system in the dry tropics of Costa Rica. A total of 120 weed species were detected, which was similar to surveys conducted in subtropical and temperate conditions. Weed species richness was highest in undisturbed field borders and lowest in rows and furrows. The area where tractors turn within the field (turn area) had similar richness compared with the borders, despite being one of the most disturbed management areas studied. The most predominant weed species were divided between generalists and species that exhibited clear preferences for management area or soil texture. Soil texture was more important for determining weed community structure than management area when considering weed species affecting weed control decisions. The results indicated that disturbance in the management area and, especially, weed control practices are critical factors affecting weed diversity, but availability of resources for weed growth such as nutrients, soil moisture, and light can mitigate some of the limitations imposed by weed control on weed diversity, especially in the turn area. Differences in weed communities between management areas within fields indicated the existence of conditions that favor key weed species, and this information can be used to anticipate their population growth and help determine when and where more intensive control should be implemented.